2018
DOI: 10.1098/rsos.180346
|View full text |Cite
|
Sign up to set email alerts
|

Vertical stress and stability of interburden over an abandoned pillar working before upward mining: a case study

Abstract: Upward mining of the residual coal seam over an abandoned pillar working is one of the effective measures to alleviate the contradiction between limited resources and increased consumption. Interburden stability over an abandoned pillar working plays a significant role in guaranteeing the safety of upward mining; however, it has not yet been extensively studied and understood. In this study, the vertical stress of the interburden over an abandoned pillar working was first investigated. The mechanical model of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 50 publications
0
5
0
Order By: Relevance
“…Feng et al considered that the failure scope of the floor strata is less than the thickness of the rock interlayers as the prerequisite for safe mining of longwall working faces, and the method for determining the feasibility of ascending mining in the strip mining area was given [22][23][24]. Bai 3 Geofluids distribution law of the mining-induced stress on the middle coal seam when above and below the working face lie the room-and-pillar mining goafs by applying a numerical simulation method [25,26]. By reviewing the existing literature, it can be found that the research results above are mainly focused on the feasibility evaluation of mining above goaf and that the failure scope of the floor rock is less than the thickness of the rock interlayers, which has been considered as the standard for mining above goaf.…”
Section: Geofluidsmentioning
confidence: 99%
“…Feng et al considered that the failure scope of the floor strata is less than the thickness of the rock interlayers as the prerequisite for safe mining of longwall working faces, and the method for determining the feasibility of ascending mining in the strip mining area was given [22][23][24]. Bai 3 Geofluids distribution law of the mining-induced stress on the middle coal seam when above and below the working face lie the room-and-pillar mining goafs by applying a numerical simulation method [25,26]. By reviewing the existing literature, it can be found that the research results above are mainly focused on the feasibility evaluation of mining above goaf and that the failure scope of the floor rock is less than the thickness of the rock interlayers, which has been considered as the standard for mining above goaf.…”
Section: Geofluidsmentioning
confidence: 99%
“…It is generally acknowledged that movements of overlying rock can be divided into three distinct zones: [44][45][46][47] the caved zone, fracture zone, and continuous deformation zone. The evolution of the overburdened structure is directly related to fracture of the rock strata; in particular, thick and hard roof formations play a key role in the development and evolution of the three zones.…”
Section: Voussoir Beam Structurementioning
confidence: 99%
“…The residual coal pillar adjusts the stress distribution characteristics of the mining face under complex geological conditions [3] and bears the load of roof fractures in the mining area [4]. The resource occurrence conditions in Shendong mining area are relatively simple.…”
Section: Introductionmentioning
confidence: 99%